Clinical profile of hypernatremia in exclusively breast-fed neonates - Devadas, Sahana; C. R., Ranjitha; Sabapathy, Sarala; K., Mallesh (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal hypernatremia is a potentially lethal condition. This study was planned to find out the predisposing factors and outcome of hypernatremia in breast feed late preterm and term neonates. Methods: In defined study period, neonates with serum sodium level >145mmol/L, who satisfies all the inclusion criteria are included in the study. The data was collected using a proforma which included clinical symptoms, risk factors for neonatal hypernatremia in addition to laboratory data. Results: The results demonstrated hypernatremia in 63 neonates with mean age of presentation being 4.5 days, mean sodium level of 154.2 and average weight loss was 13.2%. Neonates admitted at older age >7days had higher sodium concentration with mean of 162.5mmol/L. Serum sodium levels correlates positively with percentage of weight loss and correlates negatively with birth weight and was statistically significant with p value <0.05. 41(65%) of mothers were primipara, 37(58%) had delivered by LSCS and 39(62%) had lactation issues postnatally. Most common presenting symptom was jaundice in 44(71%), followed by fever in 38(61%). Conclusions: Hypernatremic dehydration can be prevented by counselling about importance of breast feeding for the mothers starting from antenatal period, early initiation of breast feeding, addressing lactation issues and monitoring daily weight.